2004
DOI: 10.1002/jcu.20076
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic umbilical vessel morphometry and perinatal outcome of fetuses with a lean umbilical cord

Abstract: Among fetuses with a sonographically lean umbilical cord, a significant relationship exists between an umbilical vein area below or equal to the 10th percentile and an adverse neonatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
0
27
0
4
Order By: Relevance
“…[4] In a study on fetuses with sonographically measured low umbilical cord cross-sectional area, Ghezzi et al , found a significant relationship between umbilical vein cross-sectional area below the 10 th percentile and adverse neonatal outcome. [5]…”
Section: Introductionmentioning
confidence: 99%
“…[4] In a study on fetuses with sonographically measured low umbilical cord cross-sectional area, Ghezzi et al , found a significant relationship between umbilical vein cross-sectional area below the 10 th percentile and adverse neonatal outcome. [5]…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord is part of fetal metabolism and it has been suggested that thickness of umbilical cord may be related to mechanism of fetal nutrition [19]. Both thick and thin umbilical cords might be dependent on quantity of Warton’s jelly and/or changing size of umbilical cord vessels in cross-sectional area [20]. Further larger studies are needed to explain probable relationship between umbilical cord, morphology of Warton’s jelly, and fetal outcome in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A lean or hypo-coiled umbilical cord has been described as a factor contributing to IUGR and perinatal complications 8 . Studies have been published on the relation between umbilical cord thickness 9 even from the first trimester and perinatal outcome, 10 and prenatal indices for coiling and umbilical cord diameter have been published 11 and related to fetal outcome, but no simple and reliable methods has been developed to evaluate umbilical cord length sonographically, only sophisticated experimental models not yet applicable in clinical medicine have been developed 12 …”
Section: Discussionmentioning
confidence: 99%